2019
DOI: 10.4103/jfmpc.jfmpc_722_19
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of planned teaching program among primary school teachers regarding awareness of learning disabilities in children

Abstract: Purpose:To assess the awareness of learning disabilities of children before and after the planned teaching program among primary school teachers.Research design:A pre-experimental, nonrandomized, one group pretest and post-test design were used.Materials and Methods:The accessible populations were all teachers working in private primary schools at Montfort Matriculation School, Chennai. Purposive sample technique was used to select the 40 samples. The instrument consisted of two sections—Part-I: demographical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Educators enquired their conformity with every declaration arraying as of 'strongly agree' to 'strongly disagree'. Item reactions was organizing enquiries so that a positive attitude is reflected by an 'agree' replies for 12 (1,4,5,6,8,10,11,14,15,17,18,19) as well as a 'disagree' answer for the lasting 8 things (2,3,7, 9,12,13,16,20). This range revealed that high score designated a more positive attitude headed for dyslexic students, whereas a low keep count specified a more negative attitude on the way to dyslexic students.…”
Section: Level Of Attitude Scoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Educators enquired their conformity with every declaration arraying as of 'strongly agree' to 'strongly disagree'. Item reactions was organizing enquiries so that a positive attitude is reflected by an 'agree' replies for 12 (1,4,5,6,8,10,11,14,15,17,18,19) as well as a 'disagree' answer for the lasting 8 things (2,3,7, 9,12,13,16,20). This range revealed that high score designated a more positive attitude headed for dyslexic students, whereas a low keep count specified a more negative attitude on the way to dyslexic students.…”
Section: Level Of Attitude Scoringmentioning
confidence: 99%
“…In regard with any committee regularly discussing about dyslexia, there were 130 (52%) teachers in the schools where have no committee regularly discussing about dyslexia and 120(48%) teachers in the schools where committee regularly discussing about dyslexia, and whereas 77(64%) had special educators and 43(36%) had mobile trainers to regularly discussing about dyslexia. In the pre-test, the majority of 150(60%) of the primary school teachers had poor knowledge (score 0-10), 70(28%) of them had average knowledge (score [11][12][13][14][15][16][17][18][19][20] and 30(12%) of them had good knowledge (score 21-30) regarding dyslexia. In consider with pre-test, 220(88%) of the primary school teachers had a negative attitude (score 20-50) and 30(12%) of them had a positive attitude (Score 51-80) towards dyslexia.…”
mentioning
confidence: 99%
See 1 more Smart Citation